Relationship Between Physical Activity Intensity and Total Cholesterol Levels in Elderly at Social Welfare Service Unit (UPTD) for Elderly, Kupang - Tenis, Linus Chaesarandy; Koamesah, Sanggwana Marthen Jacobus; Riwu, Audrey Gracelia; Rini, Desi Indria; Woda, Rahel Rara (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The increasing number of elderly individuals in Indonesia each year is accompanied by a higher prevalence of degenerative diseases, including hypercholesterolemia. However, with advancing age, elderly individuals tend to experience a decline in functional capacity, leading to reduced physical activity. This study aimed to analyze the relationship between physical activity intensity and total cholesterol levels among elderly residents at the Kupang Elderly Social Welfare Technical Implementation Unit (UPTD) in 2025. This analytical study employed a cross-sectional design involving elderly residents of the Kupang Elderly Social Welfare UPTD. Data were examined through both univariate and bivariate analyses employing the Chi-square test with a significance threshold of p < 0.05. A majority of the respondents fell into the young elderly category (60–69 years) and were mostly women. The findings revealed that the greater part of older participants showed low intensity in physical activity while having elevated total cholesterol levels. The Chi-square analysis demonstrated a meaningful connection between the intensity of physical activity and total cholesterol levels (p < 0.05). These findings suggest that a decrease in physical activity intensity correlates with an increase in total cholesterol levels among seniors. A noteworthy relationship exists between physical activity intensity and total cholesterol levels in elderly individuals at Kupang Elderly Social Welfare UPTD. Regular and appropriately tailored physical activity serves as an important strategy to maintain lipid metabolism balance and prevent cardiovascular disease risks in the elderly population.